Analisis Usaha Sayur Hidroponik di Kota Pekanbaru (Studi Kasus Green Farm Saudara Pekanbaru) - Zuprima Genta Sakti; Amnilis; Herda Gusvita (Fakultas Pertanian, Universitas Ekasakti, 2023)
The aims of this study were: (1) To describe the business profile of your Green Farm vegetables in Pekanbaru City, (2) To analyze the income and profits of your hydroponic vegetables in Pekanbaru City. This research uses a descriptive case study approach (Case Study). Determination of respondents is done intentionally (purposive). Respondents in this study were business owners (owners) and workers (employees). Methods of data collection using literature study, observation, study documentation and interviews using questionnaires. The results showed that (1) Green Farm Saudara hydroponic business in Pekanbaru City is a relatively new business in Pekanbaru City. In general, this hydroponic vegetable business license does not yet exist and has not been recorded at the Riau Provincial Agriculture Office. Production techniques include seeding, seeding using rock wool, planting, harvesting and post-harvesting. Marketing is done directly. This business uses a workforce of 1 person. Management aspects have been fulfilled, both in planning, organizing, implementing and supervising. While the financial aspects still need to be considered again systematically. (2) The income is Rp 5,510,500 /planting season and the average profit earned every 1 planting season is Rp. 2,592,729.3.